Histórias de vínculo mãe-filho: por imagens e palavras - Santos, Andreza Pinto Esquerdo (2020)
A human baby to survive and develop in a healthy way and create a sense of himself needs care and a strong connection with the parents, called a bond. This connection might be indeed the strongest of all as it will reverberate to all links in the future. In this light, the objective of the study is to understand the perception of the mother / child bond by mothers. The research, with a qualitative approach, was carried out at the Instituto da Primeira Infância (IPREDE), an institution dedicated to promoting nutrition and development in early childhood. The techniques used for this study were semi-structured interviews founded on the photovoice method, in which the participants chose a couple of photographs that had better reflected the theme, followed by the storytelling to explain what the photographs meant. The photovoice method proved to be feasible as a resource to capture stories of mother / child bonds. The bond for the mothers in the present study was manifested in various ways and at different times, with presence, absence and in the process of construction. Through images and words their expressions, affirmations, feelings and emotions were captured. The method used to analyze the narratives generated by the interviews was Paul Ricoeur's phenomenological hermeneutics. The project was submitted to the Research Ethics Committee of the Federal University of Ceará (UFC) and it has been approved. The following categories emerged from the speeches of the mothers / caregivers: (1) Bond with the unborn child, with a subcategory: the desire to generate and paternity; (2) birth: the real meet; (3) the sense of care and (4) the caregiver's sensitivity in the relationship. The desire to generate, the care, the sensitivity and the protection were the aspects that showed how the bond was established in the relationship of caregivers and their children. The study also showed that the theme has its importance beyond the individual and psychological relevance for each being while it reverberates in everyone's life with a notorious social impact.